Α-Lipoic Acid Potentiates the Anti-Inflammatory Activity of Avocado/Soybean Unsaponifiables in Chondrocyte Cultures. (July 2018) - Frondoza, Carmelita G.; Fortuno, Lowella V.; Grzanna, Mark W.; Ownby, Stacy L.; Au, Angela Y.; Rashmir-Raven, Ann M.
Objective: Pro-inflammatory mediators such as prostaglandin E-2 (PGE2 ) play major roles in the pathogenesis of osteoarthritis (OA). Although current pharmacologic treatments reduce inflammation, their prolonged use is associated with deleterious side effects prompting the search for safer and effective alternative strategies. The present study evaluated whether chondrocyte production of PGE2 can be suppressed by the combination of avocado/soybean unsaponifiables (ASU) and α-lipoic acid (LA). Design: Chondrocytes from articular cartilage of equine joints were incubated for 24 hours with: (1) control media, (2) ASU, (3) LA, or (4) ASU + LA combination. Cells were activated with lipopolysaccharide (LPS), interleukin 1β (IL-1β) or hydrogen peroxide (H2 O2 ) for 24 hours and supernatants were immunoassayed for PGE2 . Nuclear factor-kappa B (NF-κB) analyses were performed by immunocytochemistry and Western blot following 1 hour of activation with IL-1β. Results: LPS, IL-1β, or H2 O2 significantly increased PGE2 production. ASU or LA alone suppressed PGE2 production in LPS and IL-1β activated cells. Only LA alone at 2.5 µg/mL was inhibitory in H2 O2 -activated chondrocytes. ASU + LA inhibited more than either agent alone in all activated cells. ASU + LA also inhibited the IL-1β induced nuclear translocation of NF-κB. Conclusions: The present study provides evidence that chondrocyte PGE2 production can be inhibited by the combination of ASU + LA more effectively than either ASU or LA alone. Inhibition of PGE2 production is associated with the suppression of NF-κB translocation. The potent inhibitory effect of ASU + LA on PGE2 production could offer a potential advantage for a combination anti-inflammatory/antioxidant approach in the management of OA.